2019
DOI: 10.5334/gjgl.653
|View full text |Cite
|
Sign up to set email alerts
|

A Q-based approach to clausal ellipsis: Deriving the preposition stranding and island sensitivity generalisations without movement

Abstract: This paper argues that the meaning of a clausal ellipsis site can only be recovered from a syntactically derived question, regardless of whether this question is explicitly uttered or is merely pragmatically inferred. This entails that the meaning of a clausal ellipsis site cannot be recovered from an inferred question q in a language L if q is syntactically ill-formed in L. I demonstrate that this restriction on recoverability can account for Merchant’s (2001; 2004) Preposition-Stranding Generalisation and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 61 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Previous research on fragments investigated their syntactic properties and licensing conditions, and pursued almost exclusively theoretical approaches. As we observed in the introduction, information structure-based syntactic accounts of fragments (Merchant, 2004;Reich, 2007;Weir, 2014;Ott and Struckmeier, 2016;Griffiths, 2019) explain under which circumstances fragments can be used, but not why speakers choose to produce a fragment or a complete sentence. Our information-theoretic account provides a potential solution to this issue: Speakers prefer to use fragments when the omission of words that are obligatory in full sentences (like finite verbs and their arguments), which results in fragments, optimizes the form of the utterance with respect to the processing resources which are available to the hearer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous research on fragments investigated their syntactic properties and licensing conditions, and pursued almost exclusively theoretical approaches. As we observed in the introduction, information structure-based syntactic accounts of fragments (Merchant, 2004;Reich, 2007;Weir, 2014;Ott and Struckmeier, 2016;Griffiths, 2019) explain under which circumstances fragments can be used, but not why speakers choose to produce a fragment or a complete sentence. Our information-theoretic account provides a potential solution to this issue: Speakers prefer to use fragments when the omission of words that are obligatory in full sentences (like finite verbs and their arguments), which results in fragments, optimizes the form of the utterance with respect to the processing resources which are available to the hearer.…”
Section: Discussionmentioning
confidence: 96%
“…Only a few studies have looked into the questions of why speakers use fragments at all, and under which circumstances they prefer them over the corresponding full sentence. In the theoretical literature, the grammaticality of omissions has been related to information structure, in particular to the notions of focus and givenness (Merchant, 2004;Reich, 2007;Weir, 2014;Ott and Struckmeier, 2016;Griffiths, 2019). Leaving aside conceptual differences between these accounts, overall they agree on the prediction that only material that is given in an information-structural sense (Schwarzschild, 1999) can be omitted and that words that belong to the focus (see e.g., Rooth, 1992) must be realized.…”
Section: Introductionmentioning
confidence: 95%
“…For one, in and of itself it has little to say about the discursive relation between dXP and the host clause and the information‐structural properties of the dXP (but see ibid.). If and how it can account for locality effects in dislocation (including the apparent clause‐boundedness of RD) depends largely on how such facts are accounted for more generally by the theory of clausal ellipsis; see Merchant, 2004 and Griffiths, 2019 for competing views on this issue. And finally, the apparent obligatoriness of clausal ellipsis in LD and RD of the backgrounding variety could be taken to be at odds with its generally optional character, although both Ott (2014) and Ott and de Vries (2016) argue that it is not, in fact, obligatory from a strictly grammatical point of view.…”
Section: Part Ii: Resolving Cinque's Paradoxmentioning
confidence: 99%
“…Alternative analyses have suggested that what has been elided is not identical to the matrix clause (3a) (Barros et al 2014), or that there is no movement at all (3b) (e.g. Abe 2015;Ott & Struckmeier 2018;Griffiths 2019), or that nothing has in fact been deleted (3c) (e.g. Chung et al 1995;Ginzburg & Sag 2000;Culicover & Jackendoff 2005).…”
Section: Introductionmentioning
confidence: 99%